2012
DOI: 10.1007/s00192-012-1736-9
|View full text |Cite
|
Sign up to set email alerts
|

Reoperation for pelvic organ prolapse within 10 years of primary surgery for prolapse

Abstract: The reoperation rate for prolapse after primary vaginal hysterectomy and colporrhaphy appears to be modest in this series of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Studies with longer term follow-up indicate that anatomic outcomes for mesh and non-mesh apical procedures are similar [16][17][18][19]. In fact, the results from one of the most rigorous and respected RCTs concerning SC show that the rate of recurrent prolapse symptoms is similar to rates often quoted for traditional native tissue repairs and the mesh complication rate is similar to that seen with vaginal mesh procedures [19].…”
mentioning
confidence: 78%
“…Studies with longer term follow-up indicate that anatomic outcomes for mesh and non-mesh apical procedures are similar [16][17][18][19]. In fact, the results from one of the most rigorous and respected RCTs concerning SC show that the rate of recurrent prolapse symptoms is similar to rates often quoted for traditional native tissue repairs and the mesh complication rate is similar to that seen with vaginal mesh procedures [19].…”
mentioning
confidence: 78%
“…The benefits of ASC have to be weighed against the risks associated with synthetic mesh erosion, longer operating time, and longer recovery time. Although overall re‐operation rates for traditional anterior colporrhapy are variable, reported as 1–20.2%, they appear to significantly improve when concomitant apical suspension procedure is performed at time of prolapse surgery . A study of 2,756 female medicare beneficiaries who underwent anterior colporrhapy, posterior colporrhapy, or both with or without apical suspension, showed that cumulative re‐operation rates were highest among women who had isolated anterior repair (20.2%) and significantly exceeded re‐operation rates among women who had a concomitant apical support procedure (11.6%, P < 0.01) .…”
Section: Discussionmentioning
confidence: 99%
“…Although overall re-operation rates for traditional anterior colporrhapy are variable, reported as 1-20.2%, they appear to significantly improve when concomitant apical suspension procedure is performed at time of prolapse surgery. 6,[17][18][19] A study of 2,756 female medicare beneficiaries who underwent anterior colporrhapy, posterior colporrhapy, or both with or without apical suspension, showed that cumulative re-operation rates were highest among women who had isolated anterior repair (20.2%) and significantly exceeded reoperation rates among women who had a concomitant apical support procedure (11.6%, P < 0.01). 18 Again, the implicit conclusion is that persistent prolapse represents an unreinforced compartment due to failure to diagnose and treat apical support defects rather than true prolapse recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates of prolapse recurrence vary widely due to differences in study design and length of follow-up ranging from 2.3% 5,7 to 29.2% 8 . Moreover, differential findings from three RCTs resulted in discordant conclusions with respect to the best apical surgery 24 .…”
Section: Introductionmentioning
confidence: 99%